The Relationship between Serum Total Bilirubin and Severity of Hypoxic Injury in Neonatal Hypoxic–Ischemic Encephalopathy - Haga, Mitsuhiro; Kawabata, Ken; Sumiya, Wakako; Kurita, Saori; Imanishi, Toshiyuki; Kanno, Chika; Kanno, Masayuki; Kanno, Masami; Shimizu, Masaki (American Journal of Perinatology, 2020)
Introduction Bilirubin has been found to be a natural antioxidant protecting the body from oxidative stress. This study aims to investigate the severity of neonatal hypoxic injury on bilirubin levels to clarify the physiological role of bilirubin.Study Design Using lactate as a biomarker for the severity of hypoxic injury, we retrospectively analyzed the association of admission lactate levels on serum total bilirubin (TB) levels following birth in neonates with hypoxic–ischemic encephalopathy (HIE). We created a univariate linear regression model to predict TB using the admission lactate level as a predictor. We also performed a multivariate linear regression analysis to predict TB with admission lactate levels that included phenobarbital cumulative dosage, admission hematocrit, and subgaleal hemorrhage as predictor variables.Results A total of 86 patients were studied. Admission lactate levels had a significant negative effect on TB from admission to 3 days of life. The standardized regression coefficient for admission lactate on TB was −0.37 (admission), −0.42 (day 1), −0.32 (day 2), and −0.28 (day 3). A similar negative effect of admission lactate on TB levels was also observed in the multivariate linear regression model even after controlling for the other variables.Conclusion These results are consistent with the hypothesis that bilirubin functions as an antioxidant in vivo, and is consumed by scavenging free radicals in proportion to the severity of hypoxic injury.Key Points
Keywords: bilirubin; hypoxic–ischemic encephalopathy; oxidative stress; lactate